Understanding telecommunications networks - Valdar, Andy (Institution of Engineering and Technology, 2006)
This book explains how telecommunications network work. It uses straightforward language supported by copious block-schematic diagrams so that non-engineers and engineers alike can learn about the principles of fixed and mobile telecommunication networks carrying voice and data. The book covers all aspects of todays networks, including how they are planned, formed and operated, plus next generation networks and how they will be implemented. After an introductory chapter on telephony the book briefly describes all of todays networks - PSTN, mobile, cable television, the Internet etc. -and consider how they interconnect individual chapters then consider the principles, technologies and network structures relating to transmission, circuit switching, signalling and control data (including voice-over-IP) networks, and mobile networks. The important subject of numbering and addressing for telephony and IP is then covered. The book concludes with a chapter designed to pull everything together, considering architecture, quality of service and performance, operations and network evolution. Despite the rapid changes place in telecommunication today - covering customers expectations , commercial arrangements, regulation, markets and services as well as technology - This books coverage of the basic principles makes it a helpful and enduring reference for undergraduate and postgraduate students, and for professionals working in the industry.